AUDIT QUALITY IN THE BLOCKCHAIN ERA : AN INVESTIGATION OF THE IMPACT OF INDIVIDUAL AND ORGANIZATIONAL FACTORS - Wijaya, I Nyoman Agus; Setiana, Sinta; Rusyana, Finna (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
This study aims to identifying effect of individual and organizational factors to audit quality in the blockchain technologhy era. Analysis of data uses multiple linear regression. Unit of analysis in this research are auditor in Indonesia. In order to obtain primary data, we use questionnaires. The result of this research is intended to identifying the effect of individual and organizational factors to enhance Audit Quality In The Blockchain Era. We find that the business process knowledge of auditors have positively influence to the audit quality, IT Knowledge of auditors have robust influence to the audit quality, and keep to update accounting standards knowledge.